High Prevalence of Neutrophil Cytoplasmic Autoantibodies in Infants with Food Protein-Induced Proctitis/Proctocolitis: Autoimmunity Involvement? - Alena Sekerkova; Martin Fuchs; Eva Cecrdlova; Veronika Svachova; Ivana Kralova Lesna; Ilja Striz; Helena Tlaskalova-Hogenova (Journal of Immunology Research)
Background. Food protein-induced proctitis/proctocolitis (FPIP) is the most common noninfectious colitis in children in the first year of life. Along with the overall clinical symptoms, diarrhoea and rectal bleeding are the main manifestations of the disease. There is no routine noninvasive test that would be specific for this type of colitis. The aim of our study was to find a noninvasive laboratory test or tests that may be helpful in differential diagnosis of food protein-induced proctitis/proctocolitis. Methods. ANA, ANCA, ASCA, a-EMA, a-tTg, specific IgE, total IgE, IgG, IgA, IgM, and concentration of serum calprotectin were measured in a group of 25 patients with colitis and 18 children with other diagnoses. Results. Atypical-pANCA antibodies of IgG isotype were detected in the sera of 24 patients by the method of indirect immunofluorescence, and 5 patients showed also the positivity of IgA isotype. In control samples these autoantibodies were not detected. Other autoantibodies were not demonstrated in either patient or control group. Conclusions. Of the parameters tested in noninfectious colitis, atypical-pANCA on ethanol-fixed granulocytes appears to be a suitable serological marker of food protein-induced proctitis/proctocolitis and suggests a possible involvement of an autoimmune mechanisms in the pathogenesis of this disease.